N‐Heterocyclic Carbenes in Catalytic Organic Synthesis. Band 1 und 2. Science of Synthesis Workbench Edition. Herausgegeben von Steven P. Nolan und Catherine S. J. Cazin. (17th September 2018) - Peris, Eduardo
Abstract : Thieme, Stuttgart 2017. 1072 S., Broschur, 449.00 €.—ISBN 9783132414303